Which Factors Affect Functional Outcomes and Survival in Metastatic Humeral Fractures Treated With Nails? - Ebubekir Eravsar; Ali Gulec; Sadettin Ciftci; Numan Mercan; Selim Safali; Bahattin Kerem Aydin (Orthopaedic Surgery)
ABSTRACT Objective Intramedullary nailing is a treatment method for metastatic humerus fractures that stabilizes a large area while minimizing damage to the surrounding soft tissues. However, the results of this treatment may vary depending on certain factors. This study aimed to investigate the factors influencing functional outcomes and survival in patients with pathological humeral fractures treated using humeral nails. Methods This retrospective study included 41 patients who underwent humeral nailing for metastatic pathological humerus fractures between 2009 and 2024. Functional outcomes were compared based on factors such as gender, age, cancer type, another pathological fracture surgery, visceral metastases, cancer diagnosis prior to fracture, fracture type and location, and cement use, using VAS improvement, MSTS, KPS scores, and ROM measurement. Survival analysis was performed considering these same factors. Statistical analyses included the Mann–Whitney U test, Kruskal‐Wallis test, Chi‐square test, and Kaplan–Meier survival curves. Cox regression analyses were used to identify factors associated with mortality. Results In younger patients, better VAS improvement(p = 0.001), MSTS(p = 0.038), KPS(p = 0.028), and ROM(p = 0.045) were observed compared to those 65 and older. Cancer type and visceral metastases negatively impacted MSTS(p = 0.007, p = 0.049) and KPS(p = 0.002, p = 0.022). Actual fractures showed greater VAS improvement than impending fractures(p = 0.002), and shaft fractures had greater VAS improvement than proximal fractures(p = 0.037). Unknown cancer diagnosis prior to fracture led to better VAS improvement(p = 0.008), MSTS(p = 0.018), KPS(p = 0.023), and ROM(p = 0.006). Rapid growth tumor(p < 0.001) and visceral metastasis(p = 0.007) were independently associated with poor survival. No significant effects were seen for gender or cement use on functional outcomes and mortality. Conclusion Although intramedullary nails are feasible implants for humeral pathological fractures, there are significant factors that affect their functional outcomes and survival. Actual fractures and shaft fractures showed better pain relief. Patients with a known cancer diagnosis prior to fracture and older patients had poor functional outcomes. Rapid cancer type and visceral metastasis negatively affect both functional outcomes and survival. Although cement use carries a risk of thrombosis, no significant changes in mortality and functional outcomes were observed with cement use. Level of Evidence IV.